Pharmacological Characterization of the Newly Synthesized Nociceptin/Orphanin FQ-Receptor Agonist 1-[1-(1-Methylcyclooctyl)-4-piperidinyl]-2-[(3R )-3-piperidinyl]-1H-benzimidazole as an Anxiolytic Agent - Akiko Hirao; Aki Imai; Yutaka Sugie; Yoshinari Yamada; Shigeo Hayashi; Katsuo Toide (Elsevier, 2008)
Nociceptin/orphanin FQ peptide (NOP)-receptor agonists have been shown to produce anxiolytic-like effects in rodents subjected to various behavioral assays. Recently, we developed a new nonpeptide agonist of the NOP receptor, 1-[1-(1-methylcyclooctyl)-4-piperidinyl]-2-[(3R)-3-piperidinyl]-1H-benzimidazole (MCOPPB), as an anxiolytic agent. MCOPPB has a high affinity for the human NOP receptor (pKi = 10.07 ± 0.01) and selectivity for the NOP receptor over other members of the opioid receptor family: 12-, 270- and >1000-fold more selective for the NOP receptor than for the μ-, κ-, and δ-receptor, respectively. In an ex vivo binding study, MCOPPB (10 mg/kg, p.o.) inhibited signaling through the NOP receptor in the mouse brain, suggesting that it penetrated into the brain after it was orally administered. In the mouse Vogel conflict test, MCOPPB (10 mg/kg, p.o.) and diazepam (3 mg/kg, p.o.) elicited anxiolytic-like effects, although MCOPPB produced a bell-shaped response curve. In addition, MCOPPB (10 mg/kg, p.o.) was still effective as an anxiolytic agent even after repeated administration for 5 days. MCOPPB at an oral dose of 10 mg/kg did not affect locomotor activity or memory, nor did it contribute to ethanol-induced hypnosis. On the other hand, the benzodiazepine-type anxiolytic agent diazepam caused memory deficits and enhanced ethanol-induced hypnosis. These findings suggest that MCOPPB -a compound with few adverse effects on the central nervous system -is a potential therapeutic agent for the treatment of anxiety. Keywords:: nociceptin/orphanin FQ peptide (NOP) receptor, MCOPPB, non-peptide agonist, Vogel conflict test, anxiety